Differentiation, labor market and globalization. Issue 6 (17th August 2016) - Hili, Amal; Lahmandi-Ayed, Rim; Lasram, Hejer
Abstract : We consider two countries with initially one firm in each country and the possibility for each firm to invest in the other country or commercialize its products, and for workers to immigrate (Common Labor Market; CLM). Interestingly, when firms compete on the product market with no competition on the labor market (Goods' Mobility; GM), they do not differentiate their qualities. However, when competition is introduced in both markets (Foreign Investment; FI) firms differentiate their products. We compare the globalization scenarii and prove that they improve the global social welfare relative to autarky and that a cooperative choice by countries of a globalization scenario would lead to GM.